Motivations and Emotions Behind Guru Seeking: A Case Study of Thakur Anukulchandra in Bhubaneswar, Odisha - Mohapatra, Soumya (Dhaulagiri Journal of Sociology and Anthropology, 2021)
This article explores why people seek out a religious guru, with special reference to Thakur Anukulchandra and his followers in contemporary urban settings of Bhubaneswar, Odisha in India. Through an ethnographic approach, this article examines the expectations of the devotees while seeking out spirituality and what kind of emotions people go through in this process, i.e. their hopes, disappointments, social bonds created with the guru and other followers. It looks at why the followers of this tradition are attracted to this particular ideology, philosophy and its relevance in an urbane setting. The study’s rationale is to explore the complex emotional bond between the guru and the followers, the narratives of devotion, accounts of miracles performed, indices of anxiety, and the nature of well-being. Findings suggest that Thakur’s sect provides people with a meaning and purpose in life and a personal connection with the charismatic guru that helps them tide over various existential crises. By making connections between the past and the present, the organization tries to anchor people’s lives and experiences.